Muslims and humour Essays on Comedy, Joking, and Mirth in Contemporary Islamic Contexts (Bristol Bristol University Press, 2022)
muslims; humour; essays
English
Keywords: Cultural studies; Islam; Society & culture: general; muslims; humour; essays